2012
DOI: 10.1002/widm.1048
|View full text |Cite
|
Sign up to set email alerts
|

An overview of social network analysis

Abstract: Data mining is being increasingly applied to social networks. Two relevant reasons are the growing availability of large volumes of relational data, boosted by the proliferation of social media web sites, and the intuition that an individual's connections can yield richer information than his/her isolate attributes. This synergistic combination can show to be germane to a variety of applications such as churn prediction, fraud detection and marketing campaigns. This paper attempts to provide a general and succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 61 publications
0
64
0
4
Order By: Relevance
“…The node represents the individual or institution in the network, while the tie represents the content or way of communication [32,33]. Social network analysis (SNA) is the methodical analysis of social networks.…”
Section: Methodsmentioning
confidence: 99%
“…The node represents the individual or institution in the network, while the tie represents the content or way of communication [32,33]. Social network analysis (SNA) is the methodical analysis of social networks.…”
Section: Methodsmentioning
confidence: 99%
“…The various cities in a region are considered as points in the network, and the economic spatial interaction between cities is considered to be the tie. These points and lines comprise the regional economic spatial association network [45,46].…”
Section: Social Network Analysis Methodsmentioning
confidence: 99%
“…Machine learning focuses on estimation or prediction by considering an optimal model, whereas the latter concentrates on understanding the relationships between data. Recently, a few related studies applying a machine learning-based method have been reported in various research fields, such as environmental science, geomatics, and social science [39][40][41][42].…”
Section: Decision Tree Using Machine Learningmentioning
confidence: 99%